Pengaruh Keberadaan Anak Berkebutuhan Khusus Terhadap Konsentrasi dan Hasil Belajar Peserta Didik Kelas VI SD Negeri Klampok 01 - Dini Anggi Safitri; Didik Tri Setiyoko; Diah Sunarsih (Peneliti.net, 2022)
This study aims to determine the effect of the presence of children with special needs on the concentration and learning outcomes of Class VI students at SD Negeri Klampok 01. The method used in this study is a survey method with a quantitative approach, namely the type of data that can be calculated or measured directly, in the form of information. or explanation expressed in numbers or in the form of numbers. The data collection technique used is a questionnaire in the form of distributing observation sheets for children with special needs variables, questionnaires for learning concentration variables and test items on learning outcomes variables. This study was analyzed using SPSS version 16 software. Based on the results of research with t-test on children with special needs (X) on learning concentration (Y1) obtained a sig value of 0.004. so that the value of sig <0.05 and tcount 2,662 with ttable 2,045 so that the value of tcount is more than ttable. Thus, Ho1 is rejected and Ha1 is accepted, which means that children with special needs have an influence on the learning concentration of students. In the variable of children with special needs (X) on learning outcomes (Y2) with the results obtained, namely the value of 0.004 so that the sig value of 0.05 from the tcount value of 3.040 is greater than ttable 2.045. Thus Ho2 is rejected and Ha2 is accepted, which means that children with special needs have an influence on student learning outcomes.